Econometric modeling of tobacco exports in the milieu of changing global and national policy regimes: repercussions on the Indian tobacco sector - Reddy, K. Viswanatha; Paramesha, V.; Kumar, K. N. Ravi; Asci, S.; Immanuelraj, T. K.; Madhav, M. Sheshu; Sendhil, R.; Konduru, S.; Rao, K. Prabhakara; Ramasundaram, P. (Frontiers in Environmental Economics, 2024)
Tobacco, an important commercial crop, plays a crucial role in farmers' income and livelihood to a sizeable population and contributes significant exchange earnings to the Indian economy. Currently, India is the second largest tobacco producer after China with the production of 758 million kg (13% of global production) and exports around 190 million kg of tobacco (9% of global tobacco export volume). However, there are uncertainties surrounding the tobacco sector such as growing public health and environmental issues associated with tobacco production and consumption and changing national and international tobacco-related policy regimes. In this context, the current study investigates the determinants of tobacco exports and geographical shifts in export destinations over the years.The statistical models employed are co-integration, and vector error-correlation models to test the short-run and long-run dynamics relationship between tobacco exports and the explanatory variables, and the Markov chain approach. The empirical investigation identified 3 main determinants -domestic production, export price, and world demand, as major drivers, which are significant in the long run. The geographical shift is evident in major export destinations during the post-WHO-FCTC (Framework Convention on Tobacco Control). The gist of an operating environment for FCV tobacco in India is also portrayed, along with the negative attributes associated with the tobacco sector. Nevertheless, the goal of achieving the Sustainable Development Goals (SDGs), particularly SDG-3a, calls for consolidation and implementation of WHO-FCTC in all ratified countries. The empirical model suggests that India should take advantage of the export price, and global demand (India ratified WHO-FCTC-there is less scope for enhancing area). This modeling framework serves as a tool 25 to explore the possible options with a greater emphasis on export-centric tobacco production to promote an export-led production strategy in tobacco to capitalize on the international markets and augment foreign exchange revenue. However, it is important to pursue further studies to gain more insights into the tobacco economy in India.